Xlr4 as a new candidate gene underlying vulnerability to cocaine effects. (15th May 2020) - Di Segni, Matteo; D'Addario, Sebastian Luca; Babicola, Lucy; Ielpo, Donald; Lo Iacono, Luisa; Andolina, Diego; Accoto, Alessandra; Luchetti, Alessandra; Mancini, Camilla; Parisi, Chiara; D'Onofrio, Mara; Arisi, Ivan; et al.
Abstract: Although several studies have been performed in rodents, non-human primates and humans, the biological basis of vulnerability to develop cocaine addiction remains largely unknown. Exposure to critical early events (as Repeated Cross Fostering (RCF)) has been reported to increase sensitivity to cocaine effects in adult C57BL/6J female mice. Using a microarray approach, here we report data showing a strong engagement of X-linked lymphocyte-regulated 4a and 4b (Xlr4) genes in cocaine effects. The expression of Xlr4, a gene involved in chromatin remodeling and dendritic spine morphology, was reduced into the Nucleus Accumbens (NAc) of adult RCF C57BL/6J female. We used virally mediated accumbal Xlr4 down-modulation (AAVXlr4-KD) to investigate the role of this gene in vulnerability to cocaine effects. AAVXlr4-KD animals show a potentiated behavioral and neurochemical response to cocaine, reinstatement following cocaine withdrawal and cocaine-induced spine density alterations in the Medium-Sized Spiny Neurons of NAc. We propose Xlr4 as a new candidate gene mediating the cocaine effects. Highlights: Early stress affects Xlr4 gene expression in the Nucleus Accumbens (NAc) of mice. Xlr4 down-expression affects cocaine-induced Conditioned Place Preference and reinstatement. Xlr4 down-expression increases cocaine-induced dopamine release in the NAc. Xlr4 down-expression affects cocaine-induced dendritic spine density of accumbal MSNs. We suggest Xlr4 as a new candidate gene for cocaine effects vulnerability.